1997
DOI: 10.1557/proc-473-323
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Effect of Dielectric Air Gaps on Interconnect Reliability

Abstract: We present a modeling strategy for assessing the reliability cost for improved performance from modified interconnect structures. We have studied air gaps which have been deliberately introduced in the passivation between aluminum interconnect lines as a means for increasing transmission speed by decreasing dielectric capacitance. The models allow examination of tradeoffs between improved circuit performance and decreased reliability due to dielectric cracking. Stresses in the dielectric due to electromigratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…A few technology nodes later and at the same time as Cu interconnects were developed, it is amazing to observe that what was considered as an issue was reversed to develop air gap architectures and evaluate air cavities introduction within Al metal lines [5][6][7]. For instance, Ueda et al [5] demonstrated that effective dielectric constant lower than 2 could be achieved.…”
Section: Architectures and Integration Schemes For The Fabrication Ofmentioning
confidence: 99%
“…A few technology nodes later and at the same time as Cu interconnects were developed, it is amazing to observe that what was considered as an issue was reversed to develop air gap architectures and evaluate air cavities introduction within Al metal lines [5][6][7]. For instance, Ueda et al [5] demonstrated that effective dielectric constant lower than 2 could be achieved.…”
Section: Architectures and Integration Schemes For The Fabrication Ofmentioning
confidence: 99%
“…In the more Moore evolution, introduction of air cavities in copper interconnects appears as the only solution to achieve extreme low k values, decreasing significantly RC delay, crosstalk and power consumption [1]. In this way, non conformal deposition approaches have been proposed to introduce air cavities between lines [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of airgap cavities into copper interconnects is used to achieve extreme low k values, decreasing significantly RC delay, crosstalk and power consumption [1].Various airgap approaches have been proposed [2][3][4][5][6][7], but the transfer to industry requires drastic reliability targets. In order to predict the device lifetime and potential failure under thermal and electrical stress, the dielectric properties of multilevel Cu/airgap and homologous Cu/ULK interconnects were compared.…”
mentioning
confidence: 99%